Influence of psychological and symptom burden on disease activity scores in patients with rheumatoid arthritis - Sultan, Mohammad Imtiaz; Deb, Aparna; Islam, Mohammed Taherul; Saiful Arif, M.; Dey, Protyay; Bhattacharjee, Ananya; Chowdher, Mohammad Kafil Uddin; Zaman, M. Salman Ibna; Abedin, M. Jaber; Saha, Mrinal; Islam, Toufiqul (International Journal of Research in Medical Sciences, 2026)
Background: Joint disease activity indices such as DAS28, CDAI, and SDAI are important for the treatment of rheumatoid arthritis (RA). Yet, indices are influenced by subjective components, which are likely to be reflective of impaired psychological and symptom burden with the former possibly confounding true calculation of inflammatory activity. Objective was to assess the impact of psychological factors and symptom burden on composite disease activity scores in patients with RA. Methods: This cross-sectional analytical study selected 150 patients who fulfilled the criteria for diagnosis of RA by the ACR/EULAR in 2010. Clinical assessment comprised tender joint count and swollen joint count, patient global assessment, physician global assessment, ESR, and CRP. Depression and fatigue were measured by clinical examination and patient self–report. Disease activity was assessed based on DAS28, CDAI, and SDAI. Results: The mean age was 52.02±12.13 years, and 81.3% were women. In the 36.0% and 48.0% of patients, depression and fatigue were detected, respectively. The average value of DAS28 was 4.28±1.25 (mean±SD)." Depressed patients also had a higher DAS28 (4.82±1.19 versus 3.97±1.18, p<0.001), CDAI and SDAI scores. Similar results were observed for individuals reporting fatigue (p<0.001). VAS-patient correlated most closely with DAS28 (r=0.49, p<0.001), and ESR and CRP demonstrated weak but not significant degree of correlation. Conclusions: Psychosocial and symptom burden strongly contribute to the composite disease activity measures in RA. Disease activity scores must be interpreted in the context of psychosocial factors to prevent misclassification and unnecessary treatment step-up.